Virtual reality as a patient education tool in healthcare: A scoping review. Issue 7 (July 2022) - van der Kruk, Shannen R.; Zielinski, Rob; MacDougall, Hamish; Hughes-Barton, Donna; Gunn, Kate M.
Abstract: Objective: To explore what is currently known about the use of virtual reality (VR) as a patient education tool in healthcare. Methods: Arksey and O'Malley's scoping review method and the PRISMA-ScR Checklist were employed. Four peer-reviewed databases were searched (Medline, Embase, PsychINFO, the Cochrane library). Pre-defined selection criteria identified 18 studies for inclusion. Results were synthesized using a narrative approach. Results: VR as an educational tool in healthcare is feasible and acceptable, and may improve patient's knowledge about their illness and satisfaction with treatment. Most studies used the Oculus VR glasses or headset, educated patients though the use of 3D 360° VR anatomical models, and were conducted with people affected with cancer. Opportunities exist for exploring unintended consequences, and the role of VR in educating populations with lower health literacy. Conclusion: VR could assist in communicating medical information and knowledge to patients, but more research is needed, particularly to identify for whom and in what situations this method is most useful and to improve understanding about the potential unintended consequences. Practice implications: Health professionals should consider using VR to educate their patients, and researchers can use this as a road map on how to address knowledge gaps in this field. Highlights: Virtual reality (VR) as education tool increases patients' satisfaction, knowledge and understanding. VR as education tool in healthcare is generally feasible, acceptable, and useful. Research needs to determine the circumstances in which it adds most value and/or has unintended negative consequences.